Participação de receptores nicotínicos de acetilcolina alfa-7 (a7nAChR) na resposta aos danos metabólicos e inflamação hipotalâmica causados pelo consumo de dieta rica em gordura saturada : Participation of alpha-7 nicotinic acetylcholine receptors (a7nAChR) in the response to metabolic damage and hypothalamic inflammation caused by the consumption of a diet rich in saturated fat - Lopes, Priscilla Karla Fernandes, 1988- (2023)
Orientadores: Marcio Alberto Torsoni, Adriana Souza Torsoni